2021
DOI: 10.3390/app112311181
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomised, Controlled, Split-Face Clinical Trial to Assess the Safety and the Efficacy of Cold Atmospheric Plasma in the Treatment of Acne Vulgaris

Abstract: The increase in antibiotic resistance requires effective non-antibiotic therapies for acne. Cold atmospheric plasma (CAP) inactivates bacteria and improves wound healing, but its effect on acne has not been investigated. The objective of this controlled split-face study was to assess safety and efficacy of CAP in moderate acne. One side of the face received 8–10 treatments with cold helium plasma within 4–6 weeks; follow-up was two and four weeks thereafter. Acne lesions were counted, followed by global acne s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Reduction of particularly inflammatory lesions after ten CAP treatments within 4 to 6 weeks was significantly higher on the CAP treated than on the untreated side. Also, percentage of patients reporting improved aesthetics was higher for the treated than for the untreated side after treatment completion and at the 2- and 4-week follow-up [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduction of particularly inflammatory lesions after ten CAP treatments within 4 to 6 weeks was significantly higher on the CAP treated than on the untreated side. Also, percentage of patients reporting improved aesthetics was higher for the treated than for the untreated side after treatment completion and at the 2- and 4-week follow-up [43].…”
Section: Discussionmentioning
confidence: 99%
“…Atopic dermatitis, psoriasis, and herpes zoster, among others, are further skin diseases in which CAP has been successfully applied [23,[39][40][41][42]. Recently, Karrer et al [43] used a jet plasma device in a prospective, randomized, controlled, split-face trial to assess its safety and efficacy in the treatment of acne vulgaris. Reduction of particularly inflammatory lesions after ten CAP treatments within 4 to 6 weeks was significantly higher on the CAP treated than on the untreated side.…”
Section: Discussionmentioning
confidence: 99%
“… 12 A controlled split‐face study on acne patients demonstrated improved aesthetics on the treated side, with 79% of patients reporting enhancement compared to 45% on the untreated side. 13 Notably, studies by Wiegand et al., and Tae‐Hyun Lee et al., indicated that plasma reduced the growth of M. pachydermatis in vitro. 14 , 15 In this study, we initially confirmed the inhibitory effect of CAP on Malassezia yeasts in vitro and subsequently designed a prospective study to provide insights into the efficacy and safety of CAP compared to itraconazole in patients with MF.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ] Another dermatological clinical application is the treatment of acne, with encouraging results in lowering the number of active lesions. [ 12 ] Furthermore, it has been used successfully to treat cervical and vaginal precancerous conditions, shrinking the lesion and preventing recurrence. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%
“…[11] Another dermatological clinical application is the treatment of acne, with encouraging results in lowering the number of active lesions. [12] Furthermore, it has been used successfully to treat cervical and vaginal precancerous conditions, shrinking the lesion and preventing recurrence. [13] In light of all these clinically widespread and promising results, CAP could be assumed to be a straightforward technology to adapt to clinical use; however, recent studies have emphasized that the complex interactions between the plasma and the specific environment of interest (e.g., in vivo and in vitro microenvironments including cells, tissues, and microorganisms) make it difficult to control and predict the biological effects of CAP.…”
Section: Introductionmentioning
confidence: 99%